Early childhood education pre-service teachers’ perception of outdoor learning - Khairul Firdaus Ne'matullah; Rita Wong Mee Mee; Nabilah Abd Talib; Lim Seong Pek; Saturia Amiruddin; Md Rosli Ismail (International Journal of Evaluation and Research in Education (IJERE), 2024)
Outdoor learning encompasses a wide range of educational activities, from local natural play areas to formal school curriculum classes. Despite growing evidence of its benefits, outdoor learning is still underutilized in Malaysia’s early childhood education system. Hence, this study aims to investigate preservice teachers’ perceptions of the impact of outdoor learning on children’s well-being since future teachers’ perception is the most important indicator in predicting their intention to use it in the future. A quantitative approach was used, and the questionnaire was distributed to 63 pre-service teachers studying at Universiti Selangor, Malaysia. Based on the findings, the majority of respondents agree that outdoor learning benefits children’s well-being, especially their social and psychosocial well-being. Thus, this study provides insight into the significance of outdoor learning on children’s learning experiences and that it should be utilized more frequently in the classroom.